On the functional representation of partition function for quantum magnetic cluster systems - Korynevskii, N.A. (Condensed Matter Physics, 2002)
The problem of the functional representation for systems containing groups
of atoms with a non-compensated spin momentum (magnetic clusters) is
discussed. For representation of the functional of partition function a version
of the collective variables method with the “reference system” as a
zero-order approximation is used. A set of all isolated clusters are choosen
as a reference system. Intracluster interactions are described by exchange
Heisenberg-type Hamiltonian, the form of intercluster interactions depend
on the structure of the system investigated. Due to the use of the recently
introduced generalized transition operators (like well-known HubbardStasyuk
operators) an explicit form of the functional of partition function is
found. Обговорюється проблема функціонального зображення для систем, що містять групи атомів з нескомпенсованим спіновим моментом (магнітні кластери). Для зображення функціонала статистичної суми використано варіант методу колективних змінних з виділеною “системою відліку", яка відповідає нульовому наближенню. В якості системи відліку розглядається сукупність ізольованих кластерів. Внутрікластерні взаємодії описуються обмінним гамільтоніаном гайзенбергівського типу, вигляд міжкластерних взаємодій визначається структурою системи, що досліджується. Завдяки використанню попередньо впроваджених узагальнених операторів переходу (близьких до відомих операторів Хаббарда-Стасюка) отримано явну форму функціонала статистичної суми.